Academic Critical Thinking, Research Literacy and Undergraduate History. Issue 1 (1st December 2017) - Ekecrantz, Stefan
Abstract : The concept of critical thinking is pivotal in academia. Many see it as the very core of intellectual thought and the primary learning outcome of higher education. In addition to its universal merits, modern society presents challenges that arguably make this potential outcome more urgent than ever. One problem in critical thinking research and general discourse is that the concept is so broadly defined that it includes virtually anything and everything of virtue. In this article, a narrower concept of academic critical thinking is suggested as a framework for teaching and discussing critical thinking and research literacy with undergraduate History students. This, in turn, relates to an ongoing debate in critical thinking research if it is to be understood primarily as either a generic or a discipline-specific concept. Through a discussion of possible strengths and weaknesses of History in this regard, interdisciplinary critical thinking is proposed as a third way alternative to this long lived dichotomy.